2019
DOI: 10.17507/tpls.0902.01
|View full text |Cite
|
Sign up to set email alerts
|

The Limitations of Reading to Young Children in Literary Arabic: The Unspoken Struggle with Arabic Diglossia

Abstract: This interdisciplinary paper draws on findings from academic research on Arabic language diglossia demonstrating the linguistic distance between spoken Arabic, a’amiya and written Arabic, fusHa. It extends the implications of these findings to the literature on child development and reading. In this respect, it is is the first study to address the challenges of reading to children in a language diglossia situation. The paper starts by addressing the unfounded popular claim that fusHa and a’amiya are similar. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…When the three mothers read to their children, they used English books but not Arabic books because their children did not understand the formal Arabic used in books. In general, children's books are not published in a'amiya , the Arabic used in everyday communication, because publishers are reluctant to support this genre of colloquial books (Shendy, 2019). However, teachers can send Arabic or English picture books home for families to have book sharing time.…”
Section: Resultsmentioning
confidence: 99%
“…When the three mothers read to their children, they used English books but not Arabic books because their children did not understand the formal Arabic used in books. In general, children's books are not published in a'amiya , the Arabic used in everyday communication, because publishers are reluctant to support this genre of colloquial books (Shendy, 2019). However, teachers can send Arabic or English picture books home for families to have book sharing time.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, literature published in English focused more explicitly on the linguistic issues around Arabic language use in education (e.g. Shendy, 2019).…”
Section: Arabophone Countriesmentioning
confidence: 99%
“…For example, Saiegh-Haddad (2008) and Asaad and Eviatar (2014) conducted studies on letter learning and suggested that letters that correspond to sounds that do not occur in the Arabic dialects are more difficult to learn and to identify than the ones that do exist in the spoken Arabic variety of the speakers. Moreover, Tibi and Kirby (2018) pointed out that the diglossic situation of Arabic could pose a potential challenge in learning to use the language, since ammia, or dialectal Arabic is considered a child's first language (Shendy, 2019) and precedes their exposure to literary MSA in most cases. Children learning to read and write for the first time in MSA may face difficulties coping with a linguistic system that is essentially foreign (Taha, 2013;Horn, 2015).…”
Section: Introductionmentioning
confidence: 99%